Modelling and forecasting central Helsinki office rents - Kiehelä, Sami; Falkenbach, Heidi (International Journal of Strategic Property Management, 2014)
Office market modelling has attracted a mounting amount of interest among researchers and practitioners during past decades. Growing research activity in the area is not surprising considering the importance of rent on property values. Nonetheless, very little quantitative research on Finnish rental markets has been carried out. The objective of this study is to respond to that lack of research by examining office rent determination in the Helsinki central business district (CBD) in reduced form single equation context. We discover that changes in central Helsinki office rents are subject to variations in new office completions and changes in the added value of services sector. As historical fit does not necessarily translate into a satisfactory predictive fit, the forecasting adequacy of the final model is also tested by constructing out of the sample forecast over 2007-2009. We find that the model outperforms two naïve forecasting methods, but fails to perfectly trail the actual index. First Publish Online: 18 Sep 2014